Two Cases of Unilateral Ashy Dermatosis - Imanishi, Hisayoshi (S. Karger AG, 2011)
Ashy dermatosis is a typically asymptomatic disease of unknown origin that causes symmetrical gray spots to appear on the trunk and extremities. We report 2 cases of ashy dermatosis with unilateral distribution. To our knowledge, only 5 cases of ashy dermatosis with unilateral lesion have been reported so far. Case 1: an 11-year-old woman presented with asymptomatic slate-gray pigmented plaques on the left trunk and left upper arm. The skin biopsy specimen demonstrated a mild lymphohistiocytotic infiltrate in the upper dermis with epidermal and dermal melanosis. Q-Switched ruby laser did not improve such lesions. Case 2: a 21-year-old man was referred to our hospital because of asymptomatic slate-gray pigmented plaques on the left trunk and left upper arm. Histopathological findings were compatible with a mild lymphocytic infiltration with melanin incontinence in the upper dermis. The mechanism that governs unilateral distribution of ashy dermatosis, including in our cases, remains unclear.